The Effect of Gamified English Language Instruction on the Emotional Intelligence of First Grade Children - Niknezhad, Shabnam; Farab, Shiva (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to investigate the effect of gamified English language instruction on the emotional intelligence of first-grade children. Methods and Materials: A quasi-experimental design with pretest-posttest and a control group was used. The study population included first-grade students from District 2 of Tehran during the 2024–2025 academic year. Using cluster random sampling, 30 children were selected and randomly assigned to either the experimental group (n = 15) or the control group (n = 15). The data collection tool was the standardized 31-item pictorial Emotional Intelligence Questionnaire for Children (CEIT-R), which was administered before and after the intervention. The experimental group received a 10-session gamified English language instruction program, incorporating educational tools such as songs, storytelling, puzzles, magnetic boards, crafts, and Montessori materials designed to engage learners through play-based methods. The control group received no intervention. Data were analyzed using SPSS-26, employing descriptive statistics, Kolmogorov–Smirnov test for normality, Levene’s test for homogeneity of variances, Box’s M test for covariance homogeneity, multivariate analysis of covariance (MANCOVA), and between-subjects effects tests. Findings: The results of MANCOVA showed a significant effect of the intervention on total emotional intelligence and its components, including self-awareness, social awareness, self-management, and relationship management (Pillai’s Trace = 0.97, F = 244.97, p < 0.01). Between-group comparisons in the posttest revealed significant differences in favor of the experimental group across all components: self-awareness (F = 189.83, p < 0.01, η² = 0.87), social awareness (F = 138.43, p < 0.01, η² = 0.83), self-management (F = 127.05, p < 0.01, η² = 0.82), relationship management (F = 443.03, p < 0.01, η² = 0.94), and total emotional intelligence (F = 855.11, p < 0.01, η² = 0.97). Conclusion: These findings suggest that integrating playful and interactive methods into early language education can be an effective strategy for supporting emotional development in young learners.